2021
DOI: 10.1038/s41598-021-89664-9
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable plasma-resistance performance by nanocrystalline Y2O3·MgO composite ceramics for semiconductor industry applications

Abstract: Motivated by recent finding of crystallographic-orientation-dependent etching behavior of sintered ceramics, the plasma resistance of nanocrystalline Y2O3-MgO composite ceramics (YM) was evaluated for the first time. We report a remarkably high plasma etching resistance of nanostructure YM surpassing the plasma resistance of commercially used transparent Y2O3 and MgAl2O4 ceramics. The pore-free YM ceramic with grain sizes of several hundred nm was fabricated by hot press sintering, enabling theoretical maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…In a previously published study, etching was performed under mild plasma conditions (source power of 500 W and a bias power of 100 W, respectively), and it was confirmed that the surface roughness change of the nanocomposite was much smaller when chemical etching was preferentially acting. 17 The etching behavior of Y 2 O 3 is orientation-dependent erosion in which the (001) or (011) plane is preferentially attacked. 13 Figure 4c−e provides the 3D images of the etched surface morphology.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previously published study, etching was performed under mild plasma conditions (source power of 500 W and a bias power of 100 W, respectively), and it was confirmed that the surface roughness change of the nanocomposite was much smaller when chemical etching was preferentially acting. 17 The etching behavior of Y 2 O 3 is orientation-dependent erosion in which the (001) or (011) plane is preferentially attacked. 13 Figure 4c−e provides the 3D images of the etched surface morphology.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Until now, research on ceramic materials for semiconductor etching equipment has been limited to single-composition ceramics such as quartz, Y 2 O 3 , and YAG. We recently found that the Y 2 O 3 –MgO nanocomposite has an effect on the improvement of plasma etching resistance . So far, this material has only been of interest in military applications such as mid-infrared transparent ceramics, in which it minimizes light scattering by suppressing grain growth. However, recent studies have revealed that MgO may improve erosion resistance under a CF 4 plasma environment. , In this regard, a plasma chamber can be used more economically by improving the etching resistance through the incorporation of inexpensive MgO instead of using Y 2 O 3 of a single composition, which is expensive and difficult to manufacture due to the high consolidation temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] The YM composite has higher mechanical strength over their oxides. [12][13][14]16 Both Y 2 O 3 and MgO do not form solid solutions with each other and retain their identity in YM composite (<2110 • C). 15,17 The presence of phase mixture results in grain boundary pinning, which inhibits grain boundary movement and grain coarsening.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Y 2 O 3 ‐MgO (YM) composite has attracted researchers’ attention owing to its excellent mid‐IR transmittance (3–7‐μm region) and mechanical properties 12–15 . The YM composite has higher mechanical strength over their oxides 12–14,16 . Both Y 2 O 3 and MgO do not form solid solutions with each other and retain their identity in YM composite (<2110°C) 15,17 .…”
Section: Introductionmentioning
confidence: 99%